GUIDELINES FOR LEADING YOUR CONGREGATION 2017-2020 PASTOR-PARISH RELATIONS : connect the pastor, staff, and congregation. - GENERAL BOARD OF DISCIPLESHIP (COKESBURY, 2016)
Prepare leaders for their ministry roles.